POTENTIAL OF 77,78 mW RED DIODE LASER FOR PHOTODYNAMIC - Basitha Febrinda Hidayatulail; Irfan Mujahidin (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2019)
A laser is a light source that uses for any kinds of medical application. Diode Laser is one laser type using in the medical application such as Photodynamic Therapy and Photodynamic inactivation. Photodynamic Therapy is one of non-invasive therapy using for many therapies such as antimicrobial therapy, rejuvenating skin therapy, anti-aging skin therapy, etc. This therapy is using a light source with specific characteristics of wavelength in some case are using Light-sensitive molecules. This research aims to determine the potential of the diode laser for photodynamic therapy instrument. Diode Laser with wavelength value 660nm is Red Laser Diode that has main power output 79,4 mW. The application was using 1 cm clearance with the 30s of time exposure. The result showed that for Diode Laser  (λ) 660nm using 7,8x10-2 W input power produce 77,78 mW output power; has operational temperature 53.56oC and light beam 4.2 mm2.DOI : https://doi.org/10.26905/jeemecs.v2i2.3254